A study to determine significant titre-values of widal test in the diagnosis of enteric fever for a population of north Kerala, India - Gufran Ahmed M. Bijapur; Shamshuddin R. Kakkeri; Raysa N.P; Shaik Mohammed Usman (Al Ameen Medical College, 2014)
Objectives: To determine the baseline Widal titres of a study population and to propose titre-values of significance in the diagnosis of enteric fever. Background: Enteric fever is endemic in the Indian subcontinent with high prevalence rates. Etiological diagnosis of the condition is problematic due to several limitations implicit in the region. Singly run Widal test is often the only means available for a workable diagnosis. A knowledge of prevalent baseline titres is essential for its interpretation. Method: We performed the standard Widal tube agglutination test on the serum samples of 250 individuals of the local population selected by using appropriate criteria of inclusion and exclusion criteria. Results: A majority (74.8%) of the subjects were non-reactive. Prevalence of anti-TO antibody was highest (25.2%) followed by that of anti-TH antibody (15.2%), anti-AH antibody (6.8%) and anti-BH antibody (0.8%). Based on the distribution of titre values, the baseline titres determined were 40 for anti-TO and anti-TH antibodies and <20 for anti-AH and anti-BH antibodies. Any value obtained in Widal test over and above these values, i.e., ≥80 for anti-TO and anti-TH antibodies can be considered as significant. Similarly, for anti-AH and anti-BH antibodies, values of ≥20 can be considered as significant for diagnosis in an appropriate clinical setting. Conclusion: The baseline Widal titres of the local population were lower than those found in most other parts of India.